2017
DOI: 10.2298/vsp160211085v
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early treatment failure in adult hospitalized patients with community-acquired pneumonia

Abstract: Background/Aim. Early treatment failure (ETF) in patients hospitalized for community-acquired pneumonia (CAP) is associated with prolonged hospitalization, increased risk of mortality and high treatment costs. The aim of this study was to analyze the relative importance of factors influencing ETF in hospitalized adult patients with CAP that are still insufficiently explored. Methods. A retrospective case-control study was carried out on a sample of 126 adult patients treated for serious CAP at the Clinic for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Clindamycin seems capable of suppressing toxic generation in poison-elaborating isolates of microorganisms, and it obtains significant internalized concentrations in cells that eat and high concentrations in bones, both of which have raised curiosity in its application. 199…”
Section: Miscellaneous Drugs Significance Of Clindamycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Clindamycin seems capable of suppressing toxic generation in poison-elaborating isolates of microorganisms, and it obtains significant internalized concentrations in cells that eat and high concentrations in bones, both of which have raised curiosity in its application. 199…”
Section: Miscellaneous Drugs Significance Of Clindamycinmentioning
confidence: 99%
“…Although they aren't biologically connected, clindamycin and the accompanying medication lincomycin are frequently mentioned in conjunction with macrolides. 199 Despite nonlethal amounts, clindamycin may enhance bacterial interaction and autophagy. Clindamycin alters the outermost layer of bacteria by interfering with peptide production, thereby decreasing the adhesion of microbes to their host cells and boosting the intrinsic death of microorganisms.…”
Section: Mechanism Of Resistance Of Clindamycinmentioning
confidence: 99%
“…Most patients hospitalized due to CAP have a satisfactorily response to treatment, but treatment failure occurs in approximately 10% -15% of cases, and nearly 6% of patients may develop a rapidly progressive and life-threatening pneumonia. It was shown that deaths due to CAP mainly occur in patients with treatment failure with a mortality rate of > 40% (32)(33)(34). It is recently shown that severe systemic inflammatory response in patients with sepsis or severe CAP is associated with poor prognosis and deleterious outcomes (35,36).…”
Section: Introductionmentioning
confidence: 99%